PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA PELAKU UMKM DI KOMPLEKS PERTOKOAN CILINAYA CAKRANEGARA - Utami, Luh; Fitri, Syarifah Massuki; Nuada, I Wayan; Yuspiadi, Yuspiadi; Gani, Fahat Abdul; Anwar, Muazin (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Micro, Small and Medium Enterprises (MSMEs) face obstacles in preparing financial reporting due to a lack of understanding of the importance of financial recording and simple financial reports. Recording is considered difficult and considered unimportant because MSMEs are individual businesses that are directly managed by their owners. They do not understand that this simple financial report is very useful as a basis for making decisions for their future business. The aim of this community service is to increase basic understanding and knowledge of financial recording and preparing simple financial reports for MSMEs in the Cilinaya Shopping Complex, Cakranegara Village. The method used is to approach MSMEs in the Cilinaya shopping complex through direct outreach. The results of this activity are that MSME actors can apply the knowledge that has been provided and they accept the program we are implementing well and they also begin to understand that financial reports are very important in carrying out their business activities in the future.